ChemInform Abstract: Titanium‐Catalyzed Reductive Umpolung Reactions with a Metal‐Free Terminal Reducing Agent. Issue 35 (September 2015) - Frey, Georg; Hausmann, J. Niklas; Streuff, Jan
Abstract A new method for Ti‐catalyzed reductive umpolung reactions is reported that overcomes the traditional requirement for a stoichiometric metallic reductant.